Prediction of Transport Properties of R142b Using A New Intermolecular Potential - Wang, Xiao-Po; Song, Bo; Yang, Fu-Xin; Liu, Zhi-Gang (Asian Journal of Chemistry, 2012)
An iterative inversion scheme was used to determine the pair interaction potential of refrigerant R142b from a new correlation of collision integrals. According to the Chapman-Enskog theory and the Wang Chang-Uhlenbeck-de Boer scheme, transport properties of pure R142b were predicted by the new potential from 273.15 to 973.15 K at low-density, including viscosity, thermal conductivity, self-diffusion coefficient and thermal diffusion factor. The accuracy of the calculated values is estimated to be 1.5 % for viscosity, 5.0 % for thermal conductivity and 7.5 % for self-diffusion coefficient.